Perancangan Media Pembelajaran Berupa Video Mata Pelajaran Ekonomi Kelas XII Tentang Sistem Informasi Akuntansi Menggunakan Adobe Flash CS6 - Egi Pima Adha; Liza Efriyanti (Program Studi Akuntansi IKOPIN, 2022)
The educational process if it is equipped with a learning media will be more interesting and the level of achievement of learning objectives is maximized, therefore educators must make learning strategies so that in each learning that will be carried out it is not monotonous. The type of research that the author uses is research and development or also known as the ADDIE version of Research And Development (R&D), namely Analysis, Design, Develop, Implement and Evaluate. The Media Development Model used in this study is the Luther Sutopo Development Model which consists of 6 stages, namely Concept, Design, Material Collection, Assembly, Testing and Distribution. The product test used in this study is a test of validity, practicality and effectiveness. Based on the results of the validity that has been carried out by experts, the value of 1.016 is obtained with valid criteria. Based on the table of practicality test results with education expert lecturers, it can be seen that the results of the evaluation aspect obtained an average of 83.1043335 with the Very Practical category. Based on the table of effectiveness test results from several students and two lecturers, it can be seen that the results from the evaluation aspect obtained an average of 0.475, with the effectiveness category being Medium